Amantadine resistance of clade 2.3.2 H5N1 Avian Influenza Virus from Waterfowl in Indonesia - Dyah Ayu Hewajuli; NLP Indi Dharmayanti; I Wayan Teguh Wibawan (Indonesian Center for Animal Research and Development (ICARD), 2021)
The objective of this research was to know the sensitivity of H5N1 clade 2.3.2 AIV from Indonesia to antiviral drug (amantadine) through molecular and in vitro tests. The study was conducted by virus isolation and identification, nucleotide analysis, and susceptibility to the amantadine hydrocloride in MDCK cells. The study result represented that the mean EID50 isolates of H5N1 clade 2.3.2 AIV was determined of >108 EID50/ml. The analysis of phylogenetic tree of M2 gene from six viruses of H5N1 clade 2.3.2 AIV from Indonesia were closed with H5N1 clade 2.3.2 AIV avian influenza viruses from Vietnam, China, Hongkong. The substitution of M2 protein (V27I) was identified in six isolates H5N1 clade 2.3.2 AIV isolated from Indonesia. Avian influenza of clade 2.3.2 H5N1 subtype from Indonesia produced the formation of CPE and the positive HA reaction with non-toxic concentration of amantadine hydrochloride in MDCK cells. The result of genetic analysis of M2 gene for amantadine resistance was related with the results of HA test and the formation of CPE in MDCK cells. These results established that amantadine resistance have been identified in H5N1 clade 2.3.2 AIV viruses isolated from Indonesia